Improving Human Papillomavirus Vaccine Administration Using Medical-Dental Integration - Jack, Jessica L; Stein, Amy B; Podewils, Laura J; Breslin, Kristin; Hamilton, Scott; Williams, Joshua T B (Pediatrics (Evanston), 2025)
Children aged 9 years and older visit dental providers more frequently than medical providers. Routine dental visits include screenings for human papillomavirus (HPV)-related oropharyngeal cancers and provide opportunities for HPV vaccination. The objective of this project was to implement a medical-dental integration (MDI) program to enhance HPV vaccine administration among children aged 9 to 17 years being seen at dental clinics. Between June 1, 2021, and May 31, 2023, we conducted a quality improvement initiative at dental clinics within a large, integrated, safety-net health care system in Denver, Colorado. We implemented an MDI program in which dental professionals recommended the HPV vaccine and integrated medical staff administered the vaccine during the appointment. The primary outcome assessed was the HPV vaccine receipt on the same day as the dental visit. We used interrupted time series and multivariate regression models to assess the intervention's effectiveness. During the intervention period, this program reached 2781 dental visits, with 77% of children covered by Medicaid and 21% uninsured. Among them, 60% identified as Hispanic, 23% identified as Black, and 40% preferred to speak Spanish. Interrupted time series analysis revealed an immediate 9.8% improvement. The overall vaccination rate at eligible visits increased from 5.3% to 13.9% during the 1-year intervention. The adjusted odds ratio (aOR) of HPV vaccination at a dental visit was 4 times higher during the intervention (aOR, 4.37; 95% CI, 3.22-5.92) compared with preintervention. MDI was an effective intervention to increase HPV vaccination rates at a safety-net health care system.